Indra Kenz's Self-Disclosure Analysis on Social Media - Rita Herlina; Zyana Nurhaliza (Jurnal Ilmiah Komunikasi Makna, 2022)
Self-disclosure on social media by an influencer is the background of this research with the theme “Indra Kenz Self Disclosure Analysis on Social Media”. This study aims to determine Indra Kenz's self-disclosure in terms of self-awareness, benefits, and dangers. The methodology used in this research is a qualitative content analysis method with a discourse analysis approach. The data collection technique used is the Literature. The results of this study show that the self-disclosure that he shows on social media is carried out on the basis of self-awareness for the benefit of his personal branding, then the benefits are that the community looks entertained and inspired by the life story of Indra Kenz, but has the danger of being too open to social media, which has an impact on his detention for being a suspect in spreading fake news and money laundering under the guise of trading. As a suggestion, it would be better if Indra Kenz did not open up too much on social media beyond reasonable limits and it would be better if Indra Kenz did not use inappropriate words when responding or joking with netizens, because of course not everyone can accept it. well.